PHYTOSOCIOLOGY IN DANMARK - T. KRIENKE (Annali di Botanica, 1996)
As a contribution to the European Vegetation Survey, this paper reviews the development of phytosociology in Denmark. Phytosociology in Denmark was initiated by Warming and Raunkier in the 1890’s with the production of important papers on how to describe vegetation units and to measure them. The followed a long period of collection of vegetation data and development of data treatment methods, such as the similarity index by Sorensen in 1948. Few of the studies were strictly phytosociological, but rather informal floristic vegetation descriptions and ecological accounts, often with most emphasis on species-environment relationship. A few papers deal with community ecology and syntaxonomy, often a s apart of regional revisions. A stringent and consequent approach to describe plant communities in Denmark is much needed but yet to be adopted. An updated view of the past and recent types of plant communities and their ecology and status is badly need for any future planning of land use and conservation actions, management and monitoring.